2006
DOI: 10.2166/wst.2006.712
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative hydrogen production in packed-bed and packing-free upflow reactors

Abstract: Fermentative hydrogen production from a synthetic wastewater containing 10 g/L of sucrose was studied in two upflow reactors at 268C for 400 days. One reactor was filled with packing rings (RP) and the other was packing free (RF). The effect of hydraulic retention time (HRT) from 2 h to 24 h was investigated. Results showed that, under steady state, the hydrogen production rate significantly increased from 0.63 L/L/d to 5.35 L/L/d in the RF when HRT decreased from 24 h to 2 h; the corresponding rates were 0.56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
0
19
1
1
Order By: Relevance
“…According to the study, this species can produce acetic acid, succinic acid, isobutyric acid and isovaleric acid from the degradation of starch, sucrose and glucose. Li et al [43] found the presence of Prevotella spp. in fixed bed reactors used for H 2 production from sucrose at HRT 2 h. Won et al [44] verified that Prevotella spp.…”
Section: Composition Of the Microbial Communitiesmentioning
confidence: 99%
“…According to the study, this species can produce acetic acid, succinic acid, isobutyric acid and isovaleric acid from the degradation of starch, sucrose and glucose. Li et al [43] found the presence of Prevotella spp. in fixed bed reactors used for H 2 production from sucrose at HRT 2 h. Won et al [44] verified that Prevotella spp.…”
Section: Composition Of the Microbial Communitiesmentioning
confidence: 99%
“…One of the disadvantages of this method is underestimation of the true bacterial diversity due to the fact that only the most prominent DGGE bands are analyzed. Various studies have shown that DGGE bands representing LAB are one of the most dominant bands (Fang et al, 2002;Kim et al, 2006;Li et al, 2006;Wu et al, 2006;Hung et al, 2007;Ren et al, 2007;Jo et al, 2007;Lo et al, 2008;Sreela-or et al, 2011). Another method of analyzing the biodiversity of hydrogen-producing consortia is cloning and sequencing of the 16S rDNA gene amplified on the total DNA isolated from the culture probes.…”
Section: Lactic Acid Bacteria -Influence On Hydrogen Producersmentioning
confidence: 99%
“…It is noteworthy that (i) those papers discuss efficient systems of biohydrogen production and (ii) studies were performed under optimal conditions for hydrogen production (Fang et al, 2002;Kim et al, 2006;Li et al, 2006;Wu et al, 2006;Hung et al, 2007).…”
Section: Et Al 2006mentioning
confidence: 99%
“…Among the types of reactor used for continuous hydrogen production, are the CSTR [32,89,90,117,170] and several variations of hybrid and attached growth reactors, such as the Upflow Anaerobic Sludge Blanket reactor, the UASB [171], the Packed Bed Reactor, PBR [172], Anaerobic Sequencing Batch Reactor, ASBR [173], the Fixed Bed Bioreactor with Activated Carbon, the FBBAC [27], the Anaerobic Fluidized Bed Reactor, the AFBR [174,175], the Carrier-Induced Granular Sludge Bed, the CIGSB [176], Membrane Bioreactor, the MBR [50] and the Rhomboidal reactor [60]. A direct comparison of the performance of the different types of reactor configurations that have been studied in terms of hydrogen productivity is not possible, since the operational parameters (feedstocks and operating conditions) along with the reactor configuration, in all these studies, are quite different.…”
Section: Types Of Reactorsmentioning
confidence: 99%